Between horned and polled, is there a karyotypic difference in sheep? - Jamaluddin, Nurul Liyana (2017)
A karyotypic analysis was carried out on two breeds of sheep,Merino (horned) and Dorper (polled) to compare their chromosome features. Lymphocytes were extracted from blood samples and cultured in RPMI 1640 as a culture medium, supplemented with foetal bovine serum and penicillin-streptomycin. The cultures were made in duplicates, using phytohemagglutinin (PHA) and pokeweed (PWM) mitogens to stimulate lymphocytes growth. Cultures with PWM produce better quality and quantity of metaphase spreads compared with PHA. Karyotypes were constructed in accordance with the standard procedure of International Cytogenetic Nomenclature of Domestic Animal (ICNDA). The domestic sheep has a diploid number (2n)of 54. The chromosomes morphology of Merino and Dorper are indistinguishable based on their conventional karyotypes established. Both males and females have karyotypes of three pairs of submetacentric and 23 pairs of acrocentric autosomes. The X chromosome is identified as the largest acrocentric while the Y chromosome is identified as the smallest chromosome. The fundamental number (NF) for the male sheep is 60 and the female is also 60.